2013
DOI: 10.1097/cnq.0b013e3182753237
|View full text |Cite
|
Sign up to set email alerts
|

Guarding the Gut

Abstract: The postoperative period following abdominal surgery presents many challenges to patients and clinicians as recovery progresses and discharge from the intensive care unit approaches. Physiologic changes including the release of inflammatory mediators, increased fatigue and reduction in body mass, and a decline in pulmonary function occurring after abdominal surgery are often potentiated by bed rest and immobility. Evidence-based interventions have the potential to prevent pulmonary complications, wound instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Hospitals with higher rates of death after complications might focus on aggressive management of these high-risk complications with fluid management and early mobilization interventions. 36, 37 Greater surveillance among patients at increased risk of death following complications and rapid and appropriate intervention might increase the likelihood of survival. 38 Alternatively, hospitals could focus on preventing pulmonary and other high-mortality complications, such as interventions to reduce ventilator-assisted pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals with higher rates of death after complications might focus on aggressive management of these high-risk complications with fluid management and early mobilization interventions. 36, 37 Greater surveillance among patients at increased risk of death following complications and rapid and appropriate intervention might increase the likelihood of survival. 38 Alternatively, hospitals could focus on preventing pulmonary and other high-mortality complications, such as interventions to reduce ventilator-assisted pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have examined the effects of abdominal binders on CS complications (21,23,27). Some have addressed how abdominal binders impact wound healing (20,22,24) and pain medication consumption (21, 30) post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The results of 2 studies indicated that using an abdominal binder might reduce the risk of complications by enhancing patient comfort (26,27). A study by Giller, in which the effect of abdominal binders post-CS was examined, indicated no effect on post-operative pain, perceived distress, hemoglobin, hematocrit, and extent of painkiller consumption (27). Gustafson used such a binder to relieve pain the first day post-surgery; hemoglobin and hematocrit levels were unaffected (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these changes can be potentiated by prolonged bed rest. 14) In our proposed protocol, early mobilization and respiratory rehabilitation was aggressively introduced to prevent immobility and maintain pulmonary function after surgery. The protocol may have been beneficial in preventing such harmful physiological changes.…”
Section: Discussionmentioning
confidence: 99%